The transplacental passage of commonly used intrapartum antibiotics and its impact on the newborn management: A narrative review. (August 2019) - Viel-Theriault, I.; Fell, D.B.; Grynspan, D.; Redpath, S.; Thampi, N.
Abstract: Neonates exposed to intra-amniotic infection are at increased risk of early-onset sepsis. Administration of antibiotics to the mother may offer some protection, however a comprehensive description of the determinants influencing their transplacental passage and delivery to the fetus has not been performed. While penicillin G, ampicillin, cefazolin and gentamicin reach therapeutic levels in the fetal serum rapidly following maternal administration, the transfer of second-line intrapartum antimicrobials, such as vancomycin and clindamycin, is slower and less predictable. Erythromycin, used in the context of preterm premature rupture of the membranes, has suboptimal influx into the fetal compartment. This evidence is predominantly drawn from term pregnancies and situations of low infectious risk; however, prematurity may negatively influence fetal exposure to intrapartum antibiotics. Optimal fetal antimicrobial concentrations to target are poorly defined and the extent to which our review findings apply to preterm early-onset neonatal sepsis prevention is unclear. Interpretation of blood cultures drawn in neonates with expected circulating levels of maternal antimicrobials above the minimal inhibitory concentration for Group B Streptococcus is challenging despite the use of contemporary optimized blood culture media. Highlights: The transplacental passage of intrapartum antibiotics is influenced by gestational, placental and pharmacokinetic factors. Maternally-administered ampicillin, penicillin, and cefazolin rapidly achieve therapeutic levels in the fetal circulation. Understanding pharmacokinetic properties of intrapartum antibiotics can inform antimicrobial stewardship strategies in exposed neonates.